PENGINTEGRASIAN PENGETAHUAN KEBENCANAAN KE DALAM KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) DI SD SEKOTA BANDA ACEH - Khairuddin, Khairuddin; Niswanto, Niswanto (TABULARASA, 2014)
This study aims to identify the capacity of teachers to understand the knowledge of disaster, disaster and integrate knowledge mapped into the unit level curriculum, implement SBC that has been compiled into the syllabus and lesson plans, and implement the syllabus and Learning Program Plan into the learning process. The method used was a descriptive qualitative and action research. Subjects were school committee, working group supervisor, the Working Group Principals, Congress Subject Teacher and elementary school students in the city of Banda Aceh research found that teachers do not fully have the capacity of disaster knowledge and socialization of teachers SBC still not understood, there is still wrong in integrating disaster knowledge between syllabus and lesson plans and have not been able to spontaneously reflect on the knowledge of disaster awareness in the learning process.